NOUF6 Revisited: A Comprehensive Study of a Hexafluoridouranate(V) Salt. Issue 34 (14th July 2016) - Scheibe, Benjamin; Lippert, Sina; Rudel, Stefan S.; Buchner, Magnus R.; Burghaus, Olaf; Pietzonka, Clemens; Koch, Martin; Karttunen, Antti J.; Kraus, Florian
Abstract: We have synthesized NOUF6 by direct reaction of NO with UF6 in anhydrous HF (aHF). Based on the unit cell volume and powder diffraction data, the compound was previously reported to be isotypic to O2 PtF6, however, detailed structural data, such as the atom positions and all information that can be derived from those, were unavailable. We have therefore investigated the compound by using single‐crystal and powder X‐ray diffraction, IR, Raman, NMR, EPR, and photoluminescence spectroscopy, magnetic measurements, as well as chemical analysis, density determination, and quantum chemical calculations. Abstract : NOUF : The synthesis of NOUF6 by direct reaction of NO with UF6 in anhydrous HF is presented. Investigation of the crystal structure of the hexafluoridouranate(V) by X‐ray diffraction, as well as theoretical calculations have been performed (see figure) together with magnetic measurements of the compound and re‐investigation of the spectroscopic properties.